Product Design Development of Three-In-One Tote Bag Using The Kansei Engineering Method - Yuda Paripurna; Hari Purnomo (Universitas Mercu Buana, 2022)
The existing tote bag designs are often open at the top and vulnerable to pickpockets. Straps cannot be adjusted in length. Narrow straps, size, and the weight of their bags are causing pain. This study aims to develop a multifunctional tote bag to meet consumer needs to make it easier to carry goods of various sizes using only one bag. The population in this research is women and tote bag users who live in Tuban, East Java. The sample in this study was 30 tote bag users determined using a purposive sampling technique with the criteria being tote bag users for at least one month and aged 16-45 years. The data collection tool in this study is the Google Form questionnaire. The method in this study uses Kansei Engineering. The data were analyzed by SPSS 26. The results 14 Kansei words represent consumer desires for product development of multifunctional tote bags and are grouped into four factors: function, appearance, impression, and capacity. The old tote bag design is different from the three-in-one tote bag design based on the results of the Wilcoxon signed-rank test with a significance value of 4 factors < 0.05.